Efeito da aplicação de silicato de alumínio no rendimento e qualidade de sementes de soja - Salinas, Jadiyi Concepción Torales (2013)
It was conducted three research projects aimed at better understanding of the effect of aluminum silicate on yield and quality of soybean seeds as a source of silicon in the mineral nutrition and plant protection. In the first study was evaluated the effect of five doses of aluminum silicate applied via foliar as a source of silicon in the mineral nutrition acting on the yield and quality of soybean seeds produced in Arroio Grande, Rio Grande do Sul, Brazil. In the second study was evaluated the effect of different doses of aluminum silicate, silicon source, applied to the soil and leaves in yield components of soybean seeds produced in San Lorenzo, Paraguay. And the third experiment was evaluated the effect of different doses and aluminum silicate, applied via foliar and soil as a source of silicon in the mineral nutrition and plant protection, acting as seeds produced in San Lorenzo, Paraguay. The results obtained in the three studies showed that aluminum silicate applied foliar or soil had no effect on yield components. Seeds from plants that received foliar or soil application of aluminum silicate. There are changes in their physiological quality.